2023
DOI: 10.3390/biomedicines11071968
|View full text |Cite
|
Sign up to set email alerts
|

Adult IDH Wild-Type Glioblastoma Ultrastructural Investigation Suggests a Possible Correlation between Morphological Biomarkers and Ki-67 Index

Abstract: Glioblastoma is an aggressive brain tumor with an average life expectancy between 14 and 16 months after diagnosis. The Ki-67 labeling index (LI), a measure of cellular proliferation, is emerging as a prognostic marker in GBM. In this study, we investigated the ultrastructure of glioblastoma tissue from 9 patients with the same molecular profile (adult IDH wild-type glioblastoma, wild-type ATRX, and positive for TP53 expression, GFAP expression, and EGFR overexpression) to find possible ultrastructural feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
1
1
0
Order By: Relevance
“…We could confirm these findings in our study; concerning the complete cohort, higher Ki-67 values were not significantly associated with worse OS [OR: 0.21; 95% CI: 0.12-1.31; p = 0155]. Overall, Ki-67 proliferation indices seem to be valuable in some settings, e.g., differential diagnostic settings; however, they should not be over-interpreted in the clinical context [39].…”
Section: Os Pfs Mgmt Methylation and Ki-67 Proliferation Indexsupporting
confidence: 81%
“…We could confirm these findings in our study; concerning the complete cohort, higher Ki-67 values were not significantly associated with worse OS [OR: 0.21; 95% CI: 0.12-1.31; p = 0155]. Overall, Ki-67 proliferation indices seem to be valuable in some settings, e.g., differential diagnostic settings; however, they should not be over-interpreted in the clinical context [39].…”
Section: Os Pfs Mgmt Methylation and Ki-67 Proliferation Indexsupporting
confidence: 81%
“…According to data from the medical literature, genetic and molecular factors have been described to play a role in the diagnosis and prognosis of these lesions and in the effect on the invasive nature of the tumour. These include ATRX or p53 mutation [41]. Current studies have found that there is an association between IDH-1 mutations and ATRX mutations.…”
Section: Discussionmentioning
confidence: 99%